Freedom of Expression and International Criminal Law: An Analysis of The Decision to Create a Testimonial Privilege for Journalists - Buchanan, Kelly (Victoria University of Wellington Law Review, 2004)
In a recent decision, the Appeals Chamber of the International Criminal Tribunal for the Former Yugoslavia recognised a qualified privilege for war correspondents in setting out a test that the party requesting its testimony must overcome in order for the Trial Chamber to issue a subpoena. This article examines the decision and the test by comparing it to the approaches of other jurisdictions and any general principles of law that arise therefrom. It also considers whether the decision is consistent with the internationally recognised rights of freedom of expression and to a fair trial. It argues that the international tribunals should take all of these sources of law into account in formulating rules of procedure and evidence, but should also give particular regard to the purposes of international criminal justice, which relate to furthering the establishment of peace. In this context it is argued that the interests of the international criminal justice system are best served by the creation of a distinct procedural framework that contains clear and principled rules. The Appeals Chamber's formulation of a journalistic privilege not only advances this goal, but also recognises that the ability of war correspondents to report on conflicts is vitally important to the international community, including the international courts themselves. The potential impact on this ability arising from the work of the courts necessitates special consideration and a degree of protection for this group.